International cross-border surrogacy: an analysis of the Malaysian legal position - Zawawi, Majdah; Alias, Siti Aliza (Ahmad Ibrahim Kulliyyah of Law , IIUM Gombak., 2016)
This article explores the legal implications that arise out of cross border surrogacy arrangements. There is a need to examine the issues that arise out of such surrogacy arrangements because it affects the responsibilities towards the resulting child. The article discusses among others, the problems in determining the legal parents, registration, custody and citizenship of the child. It is submitted that surrogacy arrangements, especially commercial surrogacy undermines the concept of the family and such an arrangement is immoral and opposed to public policy. In discussing these issues, this article is divided into six parts. Part One looks at the legality of surrogacy arrangements in Malaysia and around the world. Once this is done, Part Two analyses the effect of surrogacy arrangements under existing Malaysian laws. This then brings the discussion to Part Three, which examines the possibility of adopting the child in Malaysia. Part Four outlines the citizenship issues that arise out of a surrogacy arrangement. Following this a brief discussion on several unsettling issues is made in Part Five. Part Six then extrapolates the notion of reproductive responsibility before the paper is concluded.